2013
DOI: 10.1038/nature11910
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosomes form at ER–mitochondria contact sites

Abstract: Autophagy is a tightly regulated intracellular bulk degradation/recycling system that has fundamental roles in cellular homeostasis. Autophagy is initiated by isolation membranes, which form and elongate as they engulf portions of the cytoplasm and organelles. Eventually isolation membranes close to form double membrane-bound autophagosomes and fuse with lysosomes to degrade their contents. The physiological role of autophagy has been determined since its discovery, but the origin of autophagosomal membranes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
1,296
5
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,486 publications
(1,404 citation statements)
references
References 34 publications
54
1,296
5
8
Order By: Relevance
“…Consistent with Atg14L dot formation on the ER, it was found that ULK1 and Atg5 also form dot-like accumulations on the ER, and that these dots are also associated with the ER when visualized by live cell imaging [20,68]. Recently, Koyama-Honda et al [69] have shown that ULK1 and Atg5 are simultaneously recruited and accumulate to form dots upon starvation, possibly through the direct interaction between FIP200 and Atg16L1 [46][47][48].…”
Section: Autophagosome Formation On the Ermentioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with Atg14L dot formation on the ER, it was found that ULK1 and Atg5 also form dot-like accumulations on the ER, and that these dots are also associated with the ER when visualized by live cell imaging [20,68]. Recently, Koyama-Honda et al [69] have shown that ULK1 and Atg5 are simultaneously recruited and accumulate to form dots upon starvation, possibly through the direct interaction between FIP200 and Atg16L1 [46][47][48].…”
Section: Autophagosome Formation On the Ermentioning
confidence: 87%
“…These two separate models, however, may be reconciled by the recent work by Hamasaki et al [68], which focuses on the contact sites between the ER and mitochondria (Figure 2). ER-mitochondria contact sites were previously known to exist and play important roles in mitochondria fission, calcium signaling, lipid transfer and so on [74].…”
Section: Er-mitochondria Contact Sitesmentioning
confidence: 89%
“…One potential mechanism behind MFN2‐induced autophagy could be linked to its unique localization at the mitochondria‐ER contact site, which is considered as a source for autophagosomal membranes during elongation (Hailey et al., 2010). Absence of mitochondria‐ER interface proteins such as MFN2 and phosphofurin acidic cluster sorting protein 2 (PACS2) prevents proper autophagosome formation in response to autophagic stimuli including starvation (Hamasaki et al., 2013) or ER stress (Muñoz et al., 2013). Moreover, in a recent study, the ER acetylation machinery directly regulates autophagy in the brain (Peng et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence supports the idea that nucleation of the isolation membrane occurs at a distinct site emanating from the endoplasmic reticulum (ER), termed the omegasome 17 , other sources of membrane contribute to autophagosome formation, including ER-Golgi intermediate compartments, ERmitochondri a junctions, mitochondria, endosomes and the plasma membrane [17][18][19][20][21][22] . Taken together, these studies highlight the complexities of autophagy initiation in mammals.…”
Section: Overview Of the Autophagic Pathwaymentioning
confidence: 99%